Data-parallel programming on MIMD computers - Hatcher, P.J.; Quinn, M.J.; Lapadula, A.J.; Seevers, B.K.; Anderson, R.J.; Jones, R.R. (IEEE transactions on parallel and distributed systems, 1991)
The implementation of two compilers for the data-parallel programming language Dataparallel C is described. One compiler generates code for Intel and nCUBE hypercube multicomputers; the other generates code for Sequent multiprocessors. A suite of Dataparallel C programs has been compiled and executed, and their execution times and speedups on the Intel iPSC/2, the nCUBE 3200 and the Sequent Symmetry are presented.< >